Pajak Bumi dan Bangunan (PBB) - Nazwa Alya Putri; Nur Eliza Siregar; Kholidatul Jamilah Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Land and Building Tax (Pajak Bumi dan Bangunan or PBB) is one of the regional taxes that plays a strategic role in increasing local revenue (Pendapatan Asli Daerah or PAD). PBB is levied on taxable objects in the form of land and/or buildings, as well as on taxpayers who own or control these objects. This study aims to analyze the role of PBB in supporting regional development, the level of public awareness in paying PBB, and the challenges in its collection process. The research uses a descriptive qualitative approach with data collected through literature studies and documentation. The results show that PBB significantly contributes to PAD, especially in areas with rapid property growth. However, there are still obstacles such as lack of public outreach, suboptimal administrative systems, and varying levels of taxpayer compliance. Therefore, efforts are needed to improve service systems, educate the public, and strengthen regulations in the implementation of PBB to ensure it is more effective and efficient in supporting regional development.